Orcid: digital identifier as permanent unique register in MEDISAN - Luisa Francisca Acosta Ortega; Xiomara Cascaret Soto; Michel Lescay Arias (Centro Provincial de Información de Ciencias Médicas, 2016)
At present, the warehouse of information sources in thousands of journals makes very difficult the correct identification and recovery of the scientific production of researchers.  During the last years, attempts of different organizations have been made to create a permanent unique register for authors, which permits to identify their articles wherever they are published and without taking into account the specificity in the author's name, publishing and processing practices in data bases, and different bibliographic description styles as well.  Among these identifiers ORCID (Open Researcher and Contribution ID) has had the greatest possibilities of becoming universal to achieve visibility and positioning of Latin-American universities in the present international context, that´s why MEDISAN will start showing the ORCID register of its authors from January 2017 on.